2022
DOI: 10.1002/ehf2.13925
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum potassium in patients hospitalized for acute heart failure

Abstract: AimWe investigated the prognostic significance of serum potassium abnormalities at discharge in patients hospitalized for acute heart failure (AHF). Methods and resultsIn a retrospective analysis, we included 926 patients hospitalized for AHF, stratified by serum potassium levels at discharge as hypokalaemia (<3.5 mEq/L), normokalaemia (3.5-5.0 mEq/L), and hyperkalaemia (>5.0 mEq/L). The primary endpoint was all-cause death at 1 year since hospital discharge. At discharge, 40 patients had hypokalaemia (4.3%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Both hypokalaemia and hyperkalaemia have been associated with worse prognosis 27,28 . Cooper et al .…”
Section: Diagnosis and Prognosismentioning
confidence: 99%
“…Both hypokalaemia and hyperkalaemia have been associated with worse prognosis 27,28 . Cooper et al .…”
Section: Diagnosis and Prognosismentioning
confidence: 99%
“…Hypokalemia at discharge in patients with acute HFpEF was associated with neither all-cause mortality nor composite events of mortality and HF-related events. 23 The SwedeHF registry demonstrated that new-onset hypokalemia was not associated with HF hospitalization in patients with HF whose baseline serum potassium concentrations were 3.5-5.0 mmol/L, although 20.3% of patients experienced at least one episode of hypokalemia. 25 Concurrently, Nishihara et al have reported that the lowest K + quartile (K + <4.1 mmol/L) at discharge was associated with cardiovascular events in patients with HFpEF.…”
Section: Hypokalemia and Hf-related Eventsmentioning
confidence: 98%
“…Common side effects or complications of loop diuretics include renal dysfunction [43] and electrolyte abnormalities (hyponatraemia, hypokalaemia, hypochloraemia, and metabolic alkalosis) [44][45][46][47], all of which are associated with worse outcomes. In particular, renal dysfunction and hypochloraemia (amongst other mechanisms) may contribute to loop diuretic resistance [48,49].…”
Section: Loop Diureticsmentioning
confidence: 99%